The efficiency of photothermal action of gold shell-isolated nanoparticles against tumor cells depends on membrane interactions - Camacho, Sabrina A. [UNESP]; Kobal, Mirella B. [UNESP]; Moreira, Lucas G. [UNESP]; Bistaffa, Maria J. [UNESP]; Roque, Thamires C. [UNESP]; Pazin, Wallance M. [UNESP]; Toledo, Karina A. [UNESP]; Oliveira, Osvaldo N. [UNESP]; Aoki, Pedro H.B. [UNESP] (Elsevier, 2022)
Photoinduced hyperthermia with nanomaterials has been proven effective in photothermal therapy (PTT) of tumor tissues, but a precise control in PTT requires determination of the molecular-level mechanisms. In this paper, we determined the mechanisms responsible for the action of photoexcited gold shell-isolated nanoparticles (AuSHINs) in reducing the viability of MCF7 (glandular breast cancer) and especially A549 (lung adenocarcinoma) cells in vitro experiments, while the photoinduced damage to healthy cells was much smaller. The photoinduced effects were more significant than using other nanomaterials, and could be explained by the different effects from incorporating AuSHINs on Langmuir monolayers from lipid extracts of tumoral (MCF7 and A549) and healthy cells. The incorporation of AuSHINs caused similar expansion of the Langmuir monolayers, but Fourier-transform infrared spectroscopy (FTIR) data of Langmuir-Schaefer films (LS) indicated distinct levels of penetration into the monolayers. AuSHINs penetrated deeper into the A549 extract monolayers, affecting the vibrational modes of polar groups and carbon chains, while in MCF7 monolayers penetration was limited to the surroundings of the polar groups. Even smaller insertion was observed for monolayers of the healthy cell extract. The photochemical reactions were modulated by AuSHINs penetration, since upon irradiation the surface area of A549 monolayer decreased owing to lipid chain cleavage by oxidative reactions. For MCF7 monolayers, hydroperoxidation under illumination led to a ca. 5% increase in surface area. The monolayers of healthy cell lipid extract were barely affected by irradiation, consistent with the lowest degree of AuSHINs insertion. In summary, efficient photothermal therapy may be devised by producing AuSHINs capable of penetrating the chain region of tumor cell membranes.
Keywords: Gold shell-isolated nanoparticles; Langmuir monolayers; Photoinduced hyperthermia; Tumoral and healthy cells